2008
DOI: 10.1086/590431
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Toll‐Like Receptor 8 Variant Is Associated with HIV Disease Restriction

Abstract: This first report of a functional TLR8 variant associated with a different clinical course of an RNA viral disease may have implications for the individual risk assessment of patients infected with HIV and other RNA viruses as well as for future HIV vaccine development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(97 citation statements)
references
References 43 publications
(33 reference statements)
6
90
0
1
Order By: Relevance
“…However, a direct role of TLR8 in innate immunity is emerging. Recent data reported HIV ssRNA sequences that are specific for TLR8 (26) and epidemiological studies showed the association of a functional TLR8 variant with HIV progression disease (27) and with pulmonary tuberculosis susceptibility (28). TLR8 activity is an important source of TNF-␣ in the sinovial membrane cultures in rheumatoid arthritis (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, a direct role of TLR8 in innate immunity is emerging. Recent data reported HIV ssRNA sequences that are specific for TLR8 (26) and epidemiological studies showed the association of a functional TLR8 variant with HIV progression disease (27) and with pulmonary tuberculosis susceptibility (28). TLR8 activity is an important source of TNF-␣ in the sinovial membrane cultures in rheumatoid arthritis (29).…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that this study was not designed (e.g., powered) to assess the association of polymorphic genes with vaccine-induced immune responses. One single nucleotide polymorphism (SNP) in TLR-8 (rs3764880) was previously reported to result in slower disease progression in HIV-infected individuals and reduced activation of the NF-B pathway (21). The functional variant of TLR-8 showed the A1G polymorphism (rs3764880) that alters the start ATG codon of TLR-8 into a GTG triplet.…”
Section: H1/ic31 Phase II Clinical Trial Designmentioning
confidence: 99%
“…Especially TLR7 and 8 which are activated via stimulation of single-stranded RNA from HIV (Barton, 2007;Biasin et al, 2010;Mogensen et al, 2010). It is known that specific Single Nucleotide Polymorphisms (SNPs) in several TLR genes regulate the risk of bacterial and viral infections and polymorphisms in TLR-8 and TLR-9 are associated with the disease progression of HIV (Bochud et al, 2007;Oh et al, 2008). In the study by Oh et al (2008) of the German cohort of HIV-positive patients, it was showed that A1G polymorphism in TLR8 gene was associated with the restriction of progression of HIV disease, which occurs via decreasing the activation of NF-Kβ (a known activator of HIV 1 replication) and increasing the production of TNF-α, IL-10, PGE2 and LTB4 cytokines which are potent suppressors of viral infections including HIV-1 (Oh et al, 2008).…”
Section: Role Of Toll Like Receptors (Tlrs) Mannose Binding Receptormentioning
confidence: 99%
“…It is known that specific Single Nucleotide Polymorphisms (SNPs) in several TLR genes regulate the risk of bacterial and viral infections and polymorphisms in TLR-8 and TLR-9 are associated with the disease progression of HIV (Bochud et al, 2007;Oh et al, 2008). In the study by Oh et al (2008) of the German cohort of HIV-positive patients, it was showed that A1G polymorphism in TLR8 gene was associated with the restriction of progression of HIV disease, which occurs via decreasing the activation of NF-Kβ (a known activator of HIV 1 replication) and increasing the production of TNF-α, IL-10, PGE2 and LTB4 cytokines which are potent suppressors of viral infections including HIV-1 (Oh et al, 2008). In contrast, the SNP's 1635A/G and 1174G/A in TLR9 were associated with rapid disease progression, high viral load and low levels a CD4+ T cell counts as was shown by Bochud et al (2007) on a Swiss cohort.…”
Section: Role Of Toll Like Receptors (Tlrs) Mannose Binding Receptormentioning
confidence: 99%